Handbook of research on generalized and hybrid set structures and applications for soft computing - John, Sunil Jacob (Advances in Computational Intelligence and Robotics (ACIR), 2016)
This book presents original research on soft computing applications for solving problems of uncertainty within the computing environment, emphasizing essential concepts on generalized and hybrid set structures that can be applied across industries for complex problem solving.